Intercalation pseudocapacitance in Bi2Se3−MnO2 nanotube composite for high electrochemical energy storage. (20th January 2021) - Pradhan, Mukul; Chakraborty, Rishika; Rudra, Siddheswar; Koley, Sudipta; Maji, Pradip K.; Nayak, Arpan Kumar; Das, Sutanu; Nandi, Upendranath
Highlights: Bi2 Se3 −MnO2 nanotube composite synthesized by redox mediated methodology. Evolution of intercalation pseudocapacitance in nanotube composite. Synergistic combination of intercalation and redox pseudocapacitance. Integrated high energy and high power density performance. Abstract: Layered materials exhibit exclusive electrochemical properties centered on interlayer spaces. However, slow kinetics and poor cycling stability restrict overall performance. A possible solution to deliver high energy storage is by interfacial modification of layered materials, which can structurally allow the occurrence of intercalation pseudocapacitance at redox-capacitance timescale. In this work, MnO2 has been intercalated in-situ in layered Bi2 Se3 for the first time to give Bi2 Se3 −MnO2 nanotube composite. Structural and morphological characterizations have been conducted elaborately by several experimental and theoretical studies. Electrokinetic measurements reveal a dominant capacitive mechanism of 69% at 60 mV s − 1 . Ex-situ XRD analysis after electrochemical charge-discharge cycles show reversible shifts in c -axis containing Bi2 Se3 (015) plane, which confirms intercalation pseudocapacitance. The nanocomposite demonstrates high specific capacitance (438 F g − 1 at 1 A g − 1 in a three-electrode system) in a wide potential window of 2 V. Moreover, a symmetric two-electrode system for Bi2 Se3 −MnO2 exhibits a high energy density of 62 Wh kg −1 and a power density of 2.7 kW kg −1 at 1 A g − 1 and 10 A g − 1, respectively, along with capacitance retention of 86% after 2000 cycles. The study gives promising direction to design integrated high energy and power density intercalation pseudocapacitive materials. Graphical abstract: Intercalation pseudocapacitance in Bi2 Se3 −MnO2 nanotube composite for high electrochemical energy storage Image, graphical abstract